ホッキョクケン コウクウキ カンソク (AAMP98) ニ オケル オゾン ノウド レンゾク カンソク - 森本, 真司; モリモト, シンジ; Morimoto, Shinji (2002)
P(論文) 航空機搭載用オゾン濃度連続観測システムを開発し，1998年3月に実施された北極圏航空機観測プログラム（AAMP 98）においてオゾン濃度の連続観測を実施した．我々が開発したシステムは，機内が与圧された航空機上で，地上から高度約13 kmまで12秒おきにオゾン濃度を観測することが可能である． 本システムを用いて得られたスバールバル諸島（ノルウェ ー ）上空 のオゾン濃度は，オゾンゾンデによる観測値と非常に良く 一致した．一方，バロー（アラスカ）からロングイヤービンまでの195 hPa等圧面上におけるオゾン濃度は，同時に観測されたCO2濃度と明瞭な逆相関を示した．これらのことから，オゾン濃度は成層圏大気のトレーサーとして成層圏–対流圏間の大気輸送過程に関する有効な情報を持つことが明らかになった． Continuous measurement of the ozone concentration was carried out on board a jet airplane as a part of the ‘Arctic Airborne Measurement Program 1998 (AAMP 98)' from March 6 to 14, 1998. A newly developed ozone measurement system used in AAMP 98 was capable of precise determination of the ozone concentration from ground level to about 13 km height every 12 s. The ozone data obtained by our system over Svalbard, Norway, agreed well with those by routine ozone sondes. The ozone and CO2 concentration data clearly showed negative correlations at a constant pressure level of 195 hPa between Barrow, U.S A. and Longyearbyen, Norway. These results suggest that the 'in situ' ozone data obtained on board an airplane provides useful information for exchange processes between the troposphere and stratosphere as a tracer of stratospheric air. departmental bulletin paper